PENGARUH PELATIHAN KERJA, KOMITMEN, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN KECAMATAN ASEMBAGUS KABUPATEN SITUBONDO - Soleha, Maulidatul Amaliatus; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This research aims (1) to determine the partial influence of work training variables, commitment variables and work discipline variables on employee performance at PT. PLN (Persero) Customer Service Unit, Asembagus District, Situbondo Regency (2) To determine the effect of job training variables, commitment variables and work discipline variables simultaneously on employee performance at PT. PLN (Persero) Customer Service Unit, Asembagus District, Situbondo Regency (3) To determine the influence of job training variables, commitment variables and work discipline variables which have a dominant influence on PT employee performance. PLN (Persero) Customer Service Unit, Asembagus District, Situbondo Regency. The method used is quantitative. The research result is a multiple linear regression equation Y = 2.025 + 0.332 + 0.341 + 0.352 + e. partially Job Training has a significant positive effect with a tcount value greater than ttable 2.270 > 2.042 or sig Î± 0.031 < 0.05, Commitment shows a tcount value greater than ttable 2.333 > 2.042 or sig Î± 0.027 <0.05, Work Discipline shows a value tcount is greater than ttable 2.436 > 2.042 or sig Î± 0.021 <0.05 Recruitment, Job Training and Position Promotion simultaneously influence the Performance of Civil Servants at the Bondowoso Regency Revenue Agency which is acceptable with a calculated F value of 6.157, a value greater than F table namely 2.92 or F count 6.157 > F table 2.92. The Work Discipline variable has the most dominant influence on Employee Performance with a value of 2.436.